2012
DOI: 10.1002/asia.201100967
|View full text |Cite
|
Sign up to set email alerts
|

Benzotriazole‐Bridged Sensitizers Containing a Furan Moiety for Dye‐Sensitized Solar Cells with High Open‐Circuit Voltage Performance

Abstract: Two new benzotriazole-bridged sensitizers are designed and synthesized (BTA-I and BTA-II) containing a furan moiety for dye-sensitized solar cells (DSSCs). Two corresponding dyes (BTA-III and BTA-IV) with a thiophene spacer were also synthesized for comparison. All of these dyes performed as sensitizers for DSSCs, and the photovoltaic performance data of these benzotriazole-bridged dyes showed a high open-circuit voltage (V(oc): 804-834 mV). Among the four dyes, DSSCs based on BTA-II, with a furan moiety and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 40 publications
2
48
0
1
Order By: Relevance
“…In most of the organic dyes the donor segment is typically an aromatic amine such as carbazole [10], phenothiazine [11], triphenylamine [12], phenoxazine [13], indoline [14] etc. It has been reported that the presence of electron accepting moieties such as diketeopyrrolopyrrole [15], benzotriazole [16], cyanovinyl [17], plays an active role of auxiliary acceptors and they serve as effective charge transporters between the donor and acceptor [18]. Typically, thiophene and its derivatives have been successfully utilized as p-conjugation bridges in the molecular design of organic dyes, due to their polarizability and overall stability [19].…”
Section: Introductionmentioning
confidence: 99%
“…In most of the organic dyes the donor segment is typically an aromatic amine such as carbazole [10], phenothiazine [11], triphenylamine [12], phenoxazine [13], indoline [14] etc. It has been reported that the presence of electron accepting moieties such as diketeopyrrolopyrrole [15], benzotriazole [16], cyanovinyl [17], plays an active role of auxiliary acceptors and they serve as effective charge transporters between the donor and acceptor [18]. Typically, thiophene and its derivatives have been successfully utilized as p-conjugation bridges in the molecular design of organic dyes, due to their polarizability and overall stability [19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the broad spectral response with high photocurrent has been easily achieved in BTD-based sensitizers, while their V OC is always limited to 670 mV1112. In contrast, the high V OC is easy to realize in benzotriazole-based sensitizers but their photocurrent becomes discouraging to some extent1415. As well known, the quantum conversion yield in response region and the spectrum coverage range determine the generation of photocurrent density.…”
Section: Resultsmentioning
confidence: 99%
“…To minimize the limitation, a concept of D−A−π−A motif was proposed for designing a new generation of efficient and stable organic sensitizers, in which an auxiliary electron-withdrawing unit was incorporated into the conjugated bridge to facilitate electron transfer from the donor to the acceptor10111213141516171819202122232425. As an electron deficient unit, the incorporated additional unit can efficiently modulate the energy levels, absorption bands, and function as a great relief of the blue shifts when the dye molecules anchored on TiO 2 anode, which is beneficial to the photocurrent generation with extending the incident photon-to-electron conversion efficiency (IPCE) onset10.…”
mentioning
confidence: 99%
“…Figure 1 a shows the action spectra of incident photon-to-current conversion efficiency (IPCE) as a function of incident wavelength for DSSCs. [18] From the EIS measurements, the radius of the larger semicircle decreases in the order CA-II > CA-I > RD-II > RD-I, indicating that the electron recombination resistance increases from RD-I, RD-II, and CA-I to CA-II and is reflected in the improvements of V oc . It is worth noting that the IPCE of RD-II keeps a high plateau at visible region until 710 nm.…”
Section: Dedication To Professor Klaus Müllen On the Occasion Of His mentioning
confidence: 94%